TheModel of theInfluential factors on the Intention of Women toPurchaseClothing from Online Stores - Ghasem Bakhshandeh; Samira Ghashghayi (مطالعات مدیریت کسب و کار هوشمند, 2020)
With the growth of e-commerce and numerous online businesses, more attention has been paid to the behavior of women who are an important part of consumers in this field. The purpose of the present study is to explore the influential factors on the intention of women to purchase clothing from online stores. In this regard, data were collected from 400 women in Khuzestan province using a questionnaire through convenience sampling. The conceptual model of the research was tested by structural equation modeling using SmartPLS3 software. The results revealed that the impacts of habitual online usage, subjective norm, and attitude toward online purchase were positive and significant on the intention to purchase online. In addition, the impact of perceived benefits on the intention to purchase online was also positive and significant. Furthermore, the results obtained from the Sobel test also revealed that attitude toward online purchase plays a mediating role between the perceived benefits and online purchase intention.